Advancement of Conceptual Change in Physics Education from 2018-2024: A Literature Review - Siska Dewi Aryani; Hera Novia; Andhy Setiawan; Achmad Samsudin (Jurnal Ilmiah Pendidikan Fisika, 2024)
Conceptual change (CC) occurs when students move from incorrect to scientifically accepted ideas. This article presents an overview of 47 international journal articles on the journal index, theoretical framework, purpose, data analysis, and research recommendations published between 2018-2024. This review resulted in five statements: 1) indexation of the journal used by the source of conceptual change studies; 2) the theoretical framework utilized in conceptual change; 3) the objectives used in conceptual change research; 4) data analysis used in research methodology; and 5) recommendations for various studies used by researchers to develop further. Based on this study, the authors recommend future empirical studies related to using a more specific theoretical framework in intervention learning, exploring deeper conceptual changes in the affective and social domains and examining the relationship between the role of metacognitive strategies and conceptual change.